PERBUATAN MELAWAN HUKUM PADA PERJANJIAN KERJASAMA YANG DIBUAT OLEH MUHAMMAD NUZUL SEBAGAI PIHAK DALAM PERJANJIAN BERDASARKAN PUTUSAN MAHKAMAH AGUNG NOMOR 3198 K/Pdt/2010 - Debby Nauli Rafeyfa S.; Tiara Frianita Putri; Gusti Bintang Maharaja; Kayla Namira R. F. Balfas; Sulastri, Sulastri (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
This study aims to analyze unlawful acts in a cooperation agreement based on Supreme Court Decision Number 3198 K/Pdt/2010, involving Muhammad Nuzul as a party to the agreement. The research focuses on identifying the elements of unlawful acts, including actions violating laws, causality, damages incurred, and errors or negligence committed. This study also discusses the court's considerations in resolving the case, including violations of the Notary Public Act, non-compliance with the validity requirements of agreements, and unfair profit distribution. The findings reveal that Muhammad Nuzul's actions constitute unlawful acts, involving abuse of office, violations of formal agreement procedures, and misuse of funds detrimental to other parties.